2020
DOI: 10.3390/su12187798
|View full text |Cite
|
Sign up to set email alerts
|

Improving Future Teachers’ Digital Competence Using Active Methodologies

Abstract: Contemporary society demands a university education based on active and participatory educational models that enable the development of competences, with digital competence being amongst the most demanded ones. This work presents the results of an educational innovation at the university level. It intends to analyse whether the implementation of an active methodology supported by technological tools in a virtual classroom contributes to students’ digital development. A quantitative methodology with a pre-exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 43 publications
(58 reference statements)
2
17
0
7
Order By: Relevance
“…Our study was based on digital competences, in accordance with Romero-García et al [71]. Previous studies on teachers' self-perceptions of such skills, have found low levels of competence [40,72,73], as well as training needs in this regard [38,39,74].…”
Section: The Need For Teacher Training On the Eco-responsible Use Of supporting
confidence: 57%
See 1 more Smart Citation
“…Our study was based on digital competences, in accordance with Romero-García et al [71]. Previous studies on teachers' self-perceptions of such skills, have found low levels of competence [40,72,73], as well as training needs in this regard [38,39,74].…”
Section: The Need For Teacher Training On the Eco-responsible Use Of supporting
confidence: 57%
“…These results could be explained not so much by the educational stage-it has been proven that what affects more the use of ICT is rather pedagogical competence and professional experience [90], as by the complexity of the contents for being understood in the earliest stages. Thus, the key to overcoming these differences could depend on the curriculum and teacher training of this stage about these contents [71]. This idea was also confirmed by the data extracted from the questionnaire, since the item designed to measure the training followed by teachers in this area received the lowest score.…”
Section: Assessment Of Differences According To the Stage: Secondary mentioning
confidence: 76%
“…En ese sentido, se hace necesario la adquisición de competencias digitales en el profesorado, asociadas a un conjunto de destrezas y capacidades que permitirán al docente la adecuada implementación y utilización de las TIC en el proceso de enseñanza aprendizaje (Romero-García et al, 2020). Uno de los estudios que permite potenciar dichas competencias es el modelo TPACK de Koehler y Mishra quienes consideran que los docentes deben mostrar competencias relacionadas con tres grandes aspectos: disciplinar, pedagógico y tecnológico (Mishra & Koehler, 2008).…”
Section: Competencias Digitales En El Profesoradounclassified
“…Along the same lines, the Council of the European Union has defined the 'European Digital Competence Framework' (DigComp) as a tool for the improvement of the digital competence of citizens [16]. The importance of these proposals lies in the link between the acquisition of certain skills and the proper use of ICT [17,18], with the aim of taking advantage of the possibilities is presents.…”
Section: Introductionmentioning
confidence: 99%